The many faces of religious truth: Hilary Putnam's pragmatic pluralism on religion - Brunsveld, Niek (Studies in philosophical theology, 2017)
Religious statements can be true or false, and are not merely arbitrary or personally meaningful. That is the core thesis of this work in pragmatist philosophy of religion. Other contemporary approaches are deficient, as they have problematic ways of understanding truth and experience. The argument in this study draws on Hilary Putnam's work in such fields as ethics, epistemology, philosophy of language and philosophy of mind. Influenced by Ludwig Wittgenstein, however, Putnam doesn't fully acknowledge how religious statements, similar to other statements, depend on an interaction of our language and the world. This would make religious truth a matter of convention. Drawing on another source of inspiration for Putnam, William James, Niek Brunsveld shows how religious claims can have truth value